2015
DOI: 10.3390/su70912149
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Ethanol Production from Common Reed (Phragmites australis) through Simultaneuos Saccharification and Fermentation

Abstract: Abstract:Phragmites australis (common reed) is a perennial grass that grows in wetlands or near inland waterways. Due to its fast-growing properties and low requirement in nutrients and water, this arboreal variety is recognized as a promising source of renewable energy although it is one of the least characterized energy crops. In this experiment, the optimization of the bioethanol production process from Phragmites australis was carried out. Raw material was first characterized according to the standard proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…The values of Y ethanol (890e7580 L ha À1 ) were estimated following equation (3), and E prod,wh (0.17 L kg À1 ) of whole-plant common reed was lower than the reported values (16.5 g and 15.8 g ethanol per 100 g dry biomass) of Cotana et al [28] because of different pretreatment methods. Based on statistical analysis, Y ethanol values from common reed at Haimen and Sheyang were significantly higher than those at Sihong due to higher biomass yields ( Table 1).…”
Section: Fraction Composition and Ethanol Yield Predictionmentioning
confidence: 96%
“…The values of Y ethanol (890e7580 L ha À1 ) were estimated following equation (3), and E prod,wh (0.17 L kg À1 ) of whole-plant common reed was lower than the reported values (16.5 g and 15.8 g ethanol per 100 g dry biomass) of Cotana et al [28] because of different pretreatment methods. Based on statistical analysis, Y ethanol values from common reed at Haimen and Sheyang were significantly higher than those at Sihong due to higher biomass yields ( Table 1).…”
Section: Fraction Composition and Ethanol Yield Predictionmentioning
confidence: 96%
“…Composition of PAS (cellulose, hemicellulose, and lignin) was detected according to the method of reported literature [14]. As a lignocellulosic feedstock, PAS has been widely studied to produce biofuel [5,6,14]. However, to the best of our knowledge, no report has investigated LA production from PAS.…”
Section: Pretreatment Of Raw Materials and Dilute Acid Hydrolysates Fmentioning
confidence: 99%
“…As a lignocellulosic feedstock, PAS has been widely studied to produce biofuel [5,6,14]. However, to the best of our knowledge, no report has investigated LA production from PAS.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, applications of biomass wastes, residues and by-products which can potentially be used as sustainable and environmental friendly materials are increasingly gaining attention in the building industry to mitigate the environmental impacts associated with the built environment [3][4][5]. Several studies in the literature have demonstrated the wide range of natural resources and biomass applications such as burning wood for heating purposes, or even growing genetically modified microbes to produce cellulosic ethanol [12][13][14][15]. Likewise, several experimental studies have been conducted to identify and analyze the potential use of biomass as building material components [16][17][18][19].…”
Section: The Challenge Of Biomass Resourcesmentioning
confidence: 99%